2018
DOI: 10.1016/s0140-6736(17)32133-5
|View full text |Cite
|
Sign up to set email alerts
|

Transparency about the outcomes of mental health services (IAPT approach): an analysis of public data

Abstract: SummaryBackgroundInternationally, the clinical outcomes of routine mental health services are rarely recorded or reported; however, an exception is the English Improving Access to Psychological Therapies (IAPT) service, which delivers psychological therapies recommended by the National Institute for Health and Care Excellence for depression and anxiety disorders to more than 537 000 patients in the UK each year. A session-by-session outcome monitoring system ensures that IAPT obtains symptom scores before and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
266
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 250 publications
(281 citation statements)
references
References 15 publications
11
266
0
4
Order By: Relevance
“…Conversely, extending therapy beyond these dose‐response intervals (up to 24 sessions; Robinson, Delgadillo, & Kellett, 2020) is warranted for patients who have shown signs of RCSI, and we strongly caution against the arbitrary restriction of treatment sessions for these cases. Prior research has shown that IAPT services that offer a low mean number of treatment sessions tend to attain poorer clinical outcomes (Clark et al, 2018), and therefore offering an adequate dose of therapy is central to effective and ethical practice (National Collaborating Centre for Mental Health, 2018). Although observing remission of symptoms is an important milestone in therapy, it is certainly not the optimal endpoint of treatment, since it is important to ensure that symptoms stabilize in the subclinical range before completing treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, extending therapy beyond these dose‐response intervals (up to 24 sessions; Robinson, Delgadillo, & Kellett, 2020) is warranted for patients who have shown signs of RCSI, and we strongly caution against the arbitrary restriction of treatment sessions for these cases. Prior research has shown that IAPT services that offer a low mean number of treatment sessions tend to attain poorer clinical outcomes (Clark et al, 2018), and therefore offering an adequate dose of therapy is central to effective and ethical practice (National Collaborating Centre for Mental Health, 2018). Although observing remission of symptoms is an important milestone in therapy, it is certainly not the optimal endpoint of treatment, since it is important to ensure that symptoms stabilize in the subclinical range before completing treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This study also contributes to enhancing transparency by making clinical outcome gathered over several years and numerous patients, public. Studying and learning from the variation in service outcomes can help develop more effective health care (Clark et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the clinical outcome, beside remission rates, results on reliable and clinical significant change were reported.This study also contributes to enhancing transparency by making clinical outcome gathered over several years and numerous patients, public. Studying and learning from the variation in service outcomes can help develop more effective health care(Clark et al, 2018).…”
mentioning
confidence: 99%
“…4 IAPT services also use a unique session-by-session outcome-monitoring system to guide clinicians' choice of procedures and assess the overall outcome of a course of therapy. 5 Within primary care, QOF rewards practices for provision of 'quality care'. 6 Under QOF, primary care is only reimbursed for one review of a patient with depression (10-35 days after diagnosis) even though regular review (every two-four weeks in the first three months and then at longer intervals) is recommended.…”
Section: How To Manage Patients Effectively Efficiently and Within Rmentioning
confidence: 99%